Giant Interatrial Septal Aneurysms Mimicking Quistic Masses. Two Cases with Different Therapeutic Options - Galrinho, A (2010)
With the recent technical improvement in echocardiography imaging (second harmonics) the number of interatrial septum aneurysms (ASA) increased and are easily recognized. We assist to an overdiagnosing number of cases and diagnostic criteria emerged to face this problem. In the great majority of the cases ASA are small and inoffensive, but as ASA is considered a risk factor for cardioembolism when associated with persistence of foramen oval (PFO), an examination by transesophageal echocardiography (TEE) for exclusion of PFO makes the sense and is a common testing in patients with cryptogenic stroke. Besides these frequent ASA, other forms exist; the authors describe two cases of uncommon and huge ASA, one mimicking a right atrial tumor and the other a quistic, hipoechoic mass. The first case was associated with mitral stenosis and was submitted to surgery and the second was closed with an Amplatzer occluder device usually used in atrial septal defect (ASD).